Pengaruh Model Pembelajaran Project Based Learning (PjBL) Berbantuan Mind Map Terhadap Kemampuan Berpikir Kreatif Mahasiswa - Ivony Sarlin Asa; Stefania Sonia Manek; Wolfgang Asindo Seran (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to test whether the use of a project based learning model assisted by mind maps has an effect on students' creative thinking abilities. The research sample consisted of 50 class A and B students using Shapiro Wilk. quantitative method with a Quasi Experimental Design and a Nonequivalent Pretest-Posttest control group design scheme. Data was collected through pretest and posttest to obtain the N-Gain Score value between the experimental class and the control class. with a sampling technique using a purposive sampling method. Data analysis was carried out using parametric statistical tests, namely the Anova Test. Data analysis results Based on the results of data analysis obtained during the research, it shows that the N-gain score for the experimental class got an average score of 80%, categorized as effective in using the project based learning model assisted by mind maps, while the control class got an average score of 21%, categorized as ineffective in using conventional learning. When testing the hypothesis using the ANOVA test, Sig 0.000 ≤ 0.05 was obtained so that there was a significant difference between the experimental class and the control class. Thus Ho is rejected and Ha is accepted. So it can be concluded that there is a significant influence of the PjBL model assisted by mind maps on students' creative thinking abilities.